PROBLEMATIKA PENDIDIKAN BUDI PEKERTI DI LEMBAGA PEMASYARAKATAN - Desinta Dwi Rapita (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2012)
The manners education is a strategic education and it is very urgentto be givenbccause it is a form of conscious effort to give the learners to behave as people who have religious faith, having good manner, having good characteristics and good qualities as well as being responsible to his society and his country. More specifically, the manner education conducted in the Class II a Children Jail Blitar (LPA Blitar) is one of the guiding efforts in order to restore children's mental and behavior to the better direction. It is expected that through this education, those children can be complete human beings, put away their dark past, knowing what they have done wrong and never do those mistakes again so that the society can accept them back. This study also aims to describe the problems faced when conducting the Manner Education in LPA Blitar, which covers the purpose of the Manner Education in LPA Blitar, the contents of the Manner Education materials in LPA Blitar, the methods and media being used in the teaching of Manner Education in LPA Blitar, the application of the evaluation of the Manner teaching and learning, the challenges faced during the teaching and learning process as well as the techniques used for overcoming the challenges in teaching Manner Education in LPA Blitar.